2011
DOI: 10.1007/s10570-011-9514-2
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cellulose films prepared from NaOH/urea/zincate aqueous solution at low temperature

Abstract: Cellulose films were successfully prepared from NaOH/urea/zincate aqueous solution precooled to -13°C by coagulating with 5% H 2 SO 4 . The cellulose solution and regenerated cellulose films were characterized with dynamic rheology, ultraviolet-visible spectroscope, scanning electron microscopy, wide angle X-ray diffraction, Fourier transform infrared (FT-IR) spectrometer, thermogravimetry and tensile testing. The results indicated that at higher temperature (above 65°C) or lower temperature (below -10°C) or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…The crystallinity values of the foam samples are shown in Table . The crystallinity increased slightly compared to that of the original cellulose sample in the presence of SM‐MMT …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The crystallinity values of the foam samples are shown in Table . The crystallinity increased slightly compared to that of the original cellulose sample in the presence of SM‐MMT …”
Section: Resultssupporting
confidence: 93%
“…Cellulose, as one of the most important natural biopolymers, can be the best option, with a special potential to prepare multifunctional materials . Regenerated cellulose products have shown some attractive properties, including a fascinating structure, biocompatibility, biodegradability, and derivable properties that introduce them as potential biodegradable packaging materials . The preparation of porous cellulose with different solvents and methods has been previously reported .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of solvents based on aqueous alkali (containing NaOH and urea) have been developed and shown to be suitable for fiber spinning, membrane and aerogel formation, cellulose blending, and homogeneous cellulose modification . A number of researchers reported that the 7 wt % NaOH/ 12 wt % urea aqueous solution pre‐cooled to −12°C has been developed as low cost solvent for rapid dissolution of cellulose . It have been proven that the presence of NaOH hydrates and urea hydrates in the aqueous solution is the key for the cellulose dissolution at low temperature .…”
Section: Introductionmentioning
confidence: 99%
“…3 However, cellulose is an intractable solid due to strong inter‐ and intra‐molecular hydrogen bonds, and some special solvents are required for its dissolution in industrial processes. In the traditional cellulose dissolution processes, only a limited number of solvent systems have been used, for example, LiCl/ N , N ‐dimethylacetamide (DMAc),4 DMSO/paraformaldehyde, N ‐methyl‐morpholine‐ N ‐oxide (NMMO),5 molten salt hydrates,6 aqueous NaOH, and NaOH/urea solutions 7. Among the above solvents mentioned, only NMMO is actually used to make cellulose fibers on an industrial level.…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional cellulose dissolution processes, only a limited number of solvent systems have been used, for example, LiCl/N,N-dimethylacetamide (DMAc), [4] DMSO/paraformaldehyde, N-methyl-morpholine-N-oxide (NMMO), [5] molten salt hydrates, [6] aqueous NaOH, and NaOH/ urea solutions. [7] Among the above solvents mentioned, only NMMO is actually used to make cellulose fibers on an industrial level. However, there are some serious disadvantages in the NMMO process, especially the high dissolution temperature and undesired side reactions.…”
Section: Introductionmentioning
confidence: 99%